MENJALIN HUBUNGAN (RELATION) DALAM PERSPEKTIF KOMUNIKASI EFEKTIF - Ahmad S Rustan (KOMUNIDA : Media Komunikasi dan Dakwah, 2015)
Human impossible to survive in a world without the involvement of communication. In communicating with others, in addition to exchange messages with each other also build relationships with one another. The relationship developed by someone who acts as a communicator, determine the success of a communication. otherwise if the braid relations can not be achieved with both, then communication is built will fail. Similarly, a mistake to interpret the symbols of other people especially other ethnic groups can lead to conflict. For that, a communicator is required to have the ability to interpret the various symbols are attached to the komunikannya or audience.